Prevalence and influencing factors of dry eye syndrome among pilots: A survey study - Mingyue Zhang; Tiebing Liu; Yanchuang Liang; Yanmin Qi; Xin Li; Qingjun Hu (PLoS ONE, 2026)
Background Dry eye syndrome (DES) is a prevalent ocular condition that significantly impacts affected individuals’ quality of life and occupational performance. This study investigates the prevalence and contributing factors of DES among pilots, which is a group particularly susceptible to environmental and occupational stressors. Methods A descriptive, observational study was conducted, which involved 794 pilots. Based on the severity of DES, these pilots were assigned into mild, moderate and severe groups. Data was collected through surveys, and analyzed using multiple linear regression, in order to determine the relationship between the DES scores and potential influencing factors. Results The study revealed that all pilots included in the present study were affected by DES, in which 88.40% of pilots experienced moderate DES and 11.60% of pilots reported severe DES. After adjusting for other covariates in the model, the multivariate analysis revealed that eyelid diseases, ocular surface disease, poor sleep quality, and fatigue were statistically significant and positively correlated to higher DES scores ( p < 0.05), while residing in the southern region and engaging in physical activities were statistically significant and negatively correlated to the DES scores ( p < 0.05). Conclusion The high prevalence of DES in pilots highlights the urgent need for tailored occupational health interventions. Strategies to mitigate DES risk should include promoting regular physical exercise, improving sleep quality, and addressing fatigue. Future research should prioritize longitudinal studies to establish causal relationships and develop targeted management approaches for this high-risk occupational group.